Krūtinkaulio pseudoartrozės po resternotomijos gydymas Strasbūro krūtinės osteosintezės sistema: klinikinis atvejis - Janilionis, Ričardas; Falcoz, Pierre-Emmanuel; Jovaišas, Vytautas; Jagelavičius, Žymantas; Valančius, Ramūnas (Lietuvos chirurgija, 2012)
Sternal pseudoarthrosis after resternotomy treated with the Strasbourg Thoracic Osteosyntheses System: a case report Sternal dehiscence is a serious complication after general thoracic and cardiac surgery. Sternal resuturing, performed by simple rewiring or technical modification of rewiring, can fail overall when the bone quality is poor or the sternum is completely destroyed. A number of different sternal closure systems consisting of plates, screws, clips, and titanium bars have been recently introduced to treat the complicated sternal dehiscence. We describe the use of the Strasbourg Thoracic Osteosyntheses System (STRATOS) to treat complicated sternal dehiscence causing chest and back pain, sternum and chest instability, which was applied for the first time in Lithuania. Key words: sternotomy, sternal pseudoarthrosis, sternal osteosynthesis, chest instability, STRATOS.